ChemInform Abstract: Cycloadditions of Noncomplementary Substituted 1, 2, 3‐Triazines. Issue 13 (March 2015) - Anderson, Erin D.; Duerfeldt, Adam S.; Zhu, Kaicheng; Glinkerman, Christopher M.; Boger, Dale L.
Abstract Cycloaddition reactions of substituted 1, 2, 3‐triazines with amidines, enamines and ynamines allow the synthesis of pyridine, pyrimidine and pyridazine derivatives.